2015
DOI: 10.2217/nnm.14.124
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Paclitaxel-Loaded Lipid Nanocapsules After Intravenous and Oral Administration on Resistant Tumor

Abstract: This study highlights the importance of efficacy studies paired to pharmacokinetic studies for nanomedicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…Combined data of the preclinical and the pharmacokinetic studies tend to indicate that the antischistosomal activity enhancement of MFS by LNCs most probably involved the relatively stable MFS-LNCs and accordingly was not solely dependent on systemic exposure to molecular MFS. Such findings corroborated those of previous studies in pointing out that classical drug PK/PD relationships should be considered prudently for oral nanomedicines [ 62 , 63 ]. In fact, the efficacy of paclitaxel against resistant tumors was shown recently to depend on the structural integrity of nanomedicines rather than the AUC post oral absorption [ 63 ], accounting for the lack of PD/PK correlations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Combined data of the preclinical and the pharmacokinetic studies tend to indicate that the antischistosomal activity enhancement of MFS by LNCs most probably involved the relatively stable MFS-LNCs and accordingly was not solely dependent on systemic exposure to molecular MFS. Such findings corroborated those of previous studies in pointing out that classical drug PK/PD relationships should be considered prudently for oral nanomedicines [ 62 , 63 ]. In fact, the efficacy of paclitaxel against resistant tumors was shown recently to depend on the structural integrity of nanomedicines rather than the AUC post oral absorption [ 63 ], accounting for the lack of PD/PK correlations.…”
Section: Discussionsupporting
confidence: 90%
“…Such findings corroborated those of previous studies in pointing out that classical drug PK/PD relationships should be considered prudently for oral nanomedicines [ 62 , 63 ]. In fact, the efficacy of paclitaxel against resistant tumors was shown recently to depend on the structural integrity of nanomedicines rather than the AUC post oral absorption [ 63 ], accounting for the lack of PD/PK correlations. Further, oral nanomedicines may increase efficacy by targeting the sites of pathology.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, the PEGylation of LNCs induced by Kolliphor ® HS15 is insufficient and the MRT of decitabine (C12) 2 -loaded LNCs has to be enhanced by the PEGylation of LNCs with a larger PEG chain. 48 Indeed, Groo et al 49 have already demonstrated that such PEGylation of LNCs enhances the MRT by a factor of 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…42 Moreover, LNCs are a potential peptide drug carrier for oral delivery as they have been shown to be stable in gastrointestinal-simulated media, 43 have demonstrated their ability to cross intestinal mucus, 44 and show improved bioavailability. 45 Moreover, the free surface of AMP-encapsulating nanoparticulate systems could allow their decoration or modification to improve their delivery to intended sites. 46 Peptide delivery still presents many challenges, but peptide-loaded RM-LNCs show great promise for various applications.…”
Section: Protease Degradation Assaymentioning
confidence: 99%